Penerapan Teori Kognitivisme dalam Meningkatkan Efektivitas Proses Pembelajaran di Sekolah : Penelitian - Tiara Indri Prameswari; Refni Jupisa; Eva Iryani (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Education plays an important role in shaping individuals and society, with cognitivism theory as one effective approach to improving the effectiveness of the learning process for elementary school students. This study aims to evaluate the effectiveness of integrating cognitivism theory into the learning process in elementary schools, with a focus on improving students' conceptual understanding, thinking skills, and academic achievement. The research method used a classroom action cycle (PTK) approach with two cycles, including initial preparation (concept introduction, lesson planning, and development of learning activities in accordance with Piaget's stages of cognitive development), implementation of strategies such as problem-solving approaches, group discussions, use of visual media as aids, and evaluation through observation, initial and final tests, and reflection for improvement. Data were processed qualitatively and quantitatively to identify patterns, changes in understanding, and the effectiveness of the method. The results showed a significant increase in student engagement, in-depth understanding of the material, and learning motivation. The conclusion of this study confirms that consistent application of cognitivism theory can improve the academic achievement of elementary school students, encouraging educators to adopt this approach to develop critical thinking, memory, and metacognitive skills, so that students are better prepared to face future challenges. This study provides valuable insights for education practitioners to design more efficient and adaptive teaching strategies.